2020
DOI: 10.15835/nbha48211883
|View full text |Cite
|
Sign up to set email alerts
|

In vitro germination and bulblet and shoot propagation for wild edible Eremurus spectabilis M.Bieb.

Abstract: Eremurus spectabilis M.Bieb is consumed as a vegetable because of its nutritious characteristics. The plants are also used for medicinal purposes, in the cut flower industry as an ornamental geophytes, and in industry as a natural adhesive. The aim of the present study was to improve the in vitro propagation protocol (in vitro germination and bulblet and shoot formation) of E. spectabilis. For this purpose, E. spectabilis seeds were in vitro germinated in four different nutrient media: Murashige and Skoog (MS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Since they are capable of initiating cell division, they are involved in the formation of meristems, giving rise to either unorganised tissue or defined organs [42]. BAP, either singly or combined with NAA, has a positive effect on shoot regeneration [22,27,42]. Based on a recent research work [43], it was revealed that the combination of BAP and NAA was a superior treatment for mico-bulb induction in Lily (Lilium longiflorum) explants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since they are capable of initiating cell division, they are involved in the formation of meristems, giving rise to either unorganised tissue or defined organs [42]. BAP, either singly or combined with NAA, has a positive effect on shoot regeneration [22,27,42]. Based on a recent research work [43], it was revealed that the combination of BAP and NAA was a superior treatment for mico-bulb induction in Lily (Lilium longiflorum) explants.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, shoot proliferation, leaf length, and the concentrations of chlorophyll a, chlorophyll b, and carotenoids were also significantly affected. Tuncer [22] reported significant differences among MS media containing different combinations of plant growth regulators (p < 0.01) on direct shoot regeneration from hypocotyl explants of E. spectabilis. To our best of knowledge, the data presented here demonstrate a complete and applicable protocol for indirect shoot regeneration in callus cultures of Foxtail lily (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations